Alokasi Biaya dari Induk Perusahaan ke Anak Perusahaan PT. Pupuk Indonesia (Persero) - Surtikanti (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
The purpose of this activity is for the basis of reference for the parent entity and subsidiaries engaged in the fertilizer and non-fertilizer industries in setting the allocation of marketing, procurement, and information technology costs appropriately. The method of implementation of devotional activities consists of classical and discussion by means of webinars. Based on the results of the activity can be seen: Allocation of costs from the Parent Entity to the Subsidiaries, in the marketing cost compartment by direct cost method, the cost allocation rate uses fixed costs and variable costs. The cost of this fee depends on the cost allocation basis. If the allocation basis is valid for 1 year and will be set annually, then the cost allocation rate uses a fixed rate, which is the amount of the allocation proportional to the sales RKAP. While the basis of allocation is fixed every period following the activities of subsidiaries, the allocation of tariffs using variable tariffs, which is a large allocation proportional to the value of sales realization.